PROPERTIES OF INTERNATIONAL ECONOMIC INTEGRATION IN MODERN SOCIETY - Ismoil Ubaidullaevich Rakhimberdiev (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes the main features of International Economic Integration. Consideration of the activities of international organizations.